2020
DOI: 10.1111/jpc.15229
|View full text |Cite
|
Sign up to set email alerts
|

Minimising Immunisation Pain of childhood vaccines: The MIP pilot study

Abstract: Aim Pain associated with immunisations can result in distress and/or anxiety for children and parents. We assessed the feasibility and acceptability of two novel devices; Coolsense (cold) and Buzzy (vibration ± cooling pads) versus standard care to minimise pain during immunisations. We also evaluated compliance to the devices and parent's perception of the effectiveness of the devices/standard care for minimising pain during immunisation. Design Open label, pilot, randomised controlled trial (RCT). Methods Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Finally, we conducted a brief literature review of articles published on related topics to compare the results of this study with those existing in the medical literature (12)(13)(14)(15)(16)(17)(18). Although we identified several studies evaluating the pain-alleviating strategies used by various intramuscular injections, most of the studies (conducted in the last decade) compared with ours showed some degree of improvement in pain M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n tolerance with the use of various distraction devices including Buzzy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we conducted a brief literature review of articles published on related topics to compare the results of this study with those existing in the medical literature (12)(13)(14)(15)(16)(17)(18). Although we identified several studies evaluating the pain-alleviating strategies used by various intramuscular injections, most of the studies (conducted in the last decade) compared with ours showed some degree of improvement in pain M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n tolerance with the use of various distraction devices including Buzzy.…”
Section: Discussionmentioning
confidence: 99%